“Is It Roast Lamb for Dinner?” Reflections on Love, Loss and a Living God - Sarah Anne Beattie (Religions)
This essay is a personal response to the questions that arose to confront my Christian faith as I attempted to navigate a way forward amidst the impact and consequences of a cancer diagnosis for, firstly, my sister and then my husband. It is a navigation that is still, and in some respects will always be, ongoing, but in reflecting on how the ‘wrong’ questions might be replaced by the ‘right’ ones, this essay seeks to retain hope as a guiding principle to light the way ahead.